EFFECTS OF MICROWAVE INCINERATED RICE HUSK ASH (MIRHA) ON HYDRATION CHARACTERISTIC AND MECAHNICAL PROPERTIES OF FOAMED CONCRETE - BAYUAJI, RIDHO BAYUAJI (2010)
The better a material is understood, the better it can be utilized. With cementbased material such as foamed concrete (FC), knowledge of the fundamental cement hydration reactions and resultant product will facilitate design, behaviour prediction, and improved performance. Water is an integral part of all cement-based materials. It contributes to the mixing and placing ability of the material, enables the hydration process, and influences material property development. As such, it is worthy of comprehensive study, for one will never fully understand cement-based material if one does not have a good grasp of the role of water in them. The study of water in FC with Microwave Incinerated Rice Husk Ash (MIRHA) as pozzolanic material is particularly interesting, for which information about the water content can be used to understand the behaviours of the product. This study was mainly focused to investigate the role MIRHA on the non-evaporable water content in the FC The mix proportion of the MIRHA FC was designed using the Taguchi method with L16 orthogonal array with five parameters, namely, MIRHA contents, water cementitious ratio (w/c), sand cement ratio (s/c), superplasticizer (SP) content, and foam content. The mixtures were tested, both in fresh and hardened states to meet technical requirement of FC. Analysis of the characteristics of concretes, namely its compressive strength, non-evaporable water (wn) by oven dry/furnace ignition (OD/FI), non-evaporable water (wn) by Thermogravimetry (TGA), dry density and porosity were conducted. The results showed that MIRHA could facilitate enhancement in FC hydration with the evidence from wn OD/FI and TGA, Calcium Hydroxide (CH) contents and change in non-evaporable water content. The degree of hydration of MIRHA FC was predicted using a model that employed non-evaporable water technique.